2013
DOI: 10.3346/jkms.2013.28.2.287
|View full text |Cite
|
Sign up to set email alerts
|

Periarticular Osteoporosis Is a Prominent Feature in Early Rheumatoid Arthritis: Estimation Using Shaft to Periarticular Bone Mineral Density Ratio

Abstract: We aimed to quantify periarticular osteoporosis and investigate its significance in 45 patients with rheumatoid arthritis (RA) and 106 controls. Dual-energy X-ray absorptiometry (DXA) was used to determine the ratio of shaft to periarticular bone mineral density (BMD) as an index of periarticular demineralization. Periarticular osteoporosis was measured by conventional radiography. The BMDs of shaft and periarticular regions in eight designated areas on proximal phalanges were quantified. Clinical variables we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…In addition, RA patients exhibited significantly lesser Tb.N and greater Tb.Sp and Tb.Sp.SD compared to controls. This was consistent with previous DXA and HR‐pQCT studies, Nominally lower cortical BMD in the distal radius was also found in RA patients; however, the difference was not significant. These findings suggested that trabecular bone changes might be more dynamic and prominent for this patient cohort.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, RA patients exhibited significantly lesser Tb.N and greater Tb.Sp and Tb.Sp.SD compared to controls. This was consistent with previous DXA and HR‐pQCT studies, Nominally lower cortical BMD in the distal radius was also found in RA patients; however, the difference was not significant. These findings suggested that trabecular bone changes might be more dynamic and prominent for this patient cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Rheumatoid arthritis (RA) is the most common autoimmune, inflammatory joint disease, characterized primarily by chronic inflammation of synovial joints, bone and cartilage erosion and joint damage. Typically, patients initially develop periarticular osteopenia around the inflamed joints, the earliest feature of disease progression, and later develop marginal erosions which can lead to irreversible structural and functional joint impairment and generalized osteoporosis which may increase fracture risk . Metacarpal heads (MCPs), specifically the second and third MCPs (MCP2, MCP3), are particularly susceptible to RA‐related bone loss, probably due to anatomic and biomechanical factors .…”
Section: Introductionmentioning
confidence: 99%
“…18 A study focusing on young patients with RA. 19,20 In our study, we found that patients diagnosed with RA had significantly reduced bone mass (osteopenia) in spine and FN 21.6%, 28.3% respectively, this is close to Haungeberg et al, In a study of RA patient aged 20-70 years with a mean disease duration of 13 years, found the prevalence of reduced bone mass was 27.6% at FN, and 31.6% at LS. 14 The etiology of reduced bone mass in RA is multifactorial, including lifestyle risk factors and disease-related determinants.…”
Section: Resultssupporting
confidence: 90%
“…Several studies support that hand bone loss occurs early in the disease process and more rapidly than at the hip and spine [4,10,23,24,26,34] . Ten studies demonstrated that hand bone loss was higher in patients with RA than matched healthy controls and patients with other rheumatic diseases [13][14][15][16][17][18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies showed that patients with RA had significantly lower hand BMD compared with matched healthy controls or patients with other rheumatic diseases [13][14][15][16][17][18][19][20][21][22] . Similarly, five longitudinal studies reported hand bone loss was higher in patients with RA than in matched healthy controls or patients with other rheumatic diseases, including spondyloarthropathies or [7] CS RA: 100 F 53.…”
Section: Researchmentioning
confidence: 99%